2020
DOI: 10.1038/s41598-020-71996-7
|View full text |Cite
|
Sign up to set email alerts
|

Poor prognosis of NSCLC located in lower lobe is partly mediated by lower frequency of EGFR mutations

Abstract: It is controversial whether a tumor located in the lower lobe is related with worse outcome of non-small cell lung cancer (NSCLC). This study aimed to clarify the prognostic role of primary tumor location in NSCLC. Patients newly diagnosed with NSCLC in a tertiary referral hospital from January 2011 to December 2014 were followed up for 5 years. Of the 2,289 NSCLC cases, 911 (39.8%) cases pertained to lower lobe cancers. Patients with lower lobe cancer showed a higher all-cause mortality rate than those with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…In locally advanced NSCLC, lower lung lobe locations have been associated with significantly poorer outcome compared to other lung lobe locations for patients treated with chemoradiotherapy 2 as well as for patients treated with definitive radiation therapy 20 . For resectable stage IIIA NSCLC patients, contradicting results have been reported 3 , 19 , 21 . Proximity of lower lobe tumors favors to spread to the subcarinal station or contralateral hilar lymph nodes, causing in particular in advanced tumor stage a spread to central airway or mediastinum 3 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In locally advanced NSCLC, lower lung lobe locations have been associated with significantly poorer outcome compared to other lung lobe locations for patients treated with chemoradiotherapy 2 as well as for patients treated with definitive radiation therapy 20 . For resectable stage IIIA NSCLC patients, contradicting results have been reported 3 , 19 , 21 . Proximity of lower lobe tumors favors to spread to the subcarinal station or contralateral hilar lymph nodes, causing in particular in advanced tumor stage a spread to central airway or mediastinum 3 .…”
Section: Discussionmentioning
confidence: 89%
“…More commonly, tumor location was studied in relation to lobe location. Primary tumors located in the lower lobe were significantly associated with higher mortality rate in 2,289 NSCLC patients of all stages and treated with curative intent or palliative intent with surgery, radiotherapy or chemotherapy (48.6% vs. 40.3%, p < 0.001) 19 . In locally advanced NSCLC, lower lung lobe locations have been associated with significantly poorer outcome compared to other lung lobe locations for patients treated with chemoradiotherapy 2 as well as for patients treated with definitive radiation therapy 20 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The covariate can point to NSCLC on the lower left node of the lung. Studies have observed that lung cancer on the lower lobe or lower left lobe has worse survival [41, 42]. The covariate could be pointing to a severe conditions related to lung and other problems that indicate poor overall health.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, due to the promotion of smoking cessation education, early screening work, and the progress Gr- Evidence-Based Complementary and Alternative Medicine of treatment fields (such as targeted therapy, immunotherapy, etc. ), the mortality rate of lung cancer has shown a rapid trend of decline [26]. However, the current five-year survival rate remains low.…”
Section: Discussionmentioning
confidence: 99%